The Contribution of Leg Muscle Power and Ankle Coordination to the Long-Distance Kicking Ability of Extracurricular Students of SMPN 25 Pekanbaru: Kontribusi Power Otot Tungkai Dan Koordinasi Mata Kaki Terhadap Kemampuan Tendangan Jarak Jauh Siswa Ekstrakurikuler SMPN 25 Pekanbaru - Ary Susanto; Kamarudin Kamarudin (Badnur Medisa Group, 2022)
The purpose of this study was to determine the contribution of leg muscle power and eye-foot coordination to the long-distance kicking ability of soccer extracurricular students at Junior High school 25 Pekanbaru. The type of this research is multiple correlation. The population and sample in this study were 18 students of football extracurricular at Junior High school 25 Pekanbaru. The research instrument used was a leg muscle power test (standing broad jump) and an eye-foot coordination test as well as a soccer long-distance kick test. Based on the results of this study, the conclusions obtained in this study are: there is a contribution of leg muscle power to the long-distance kick ability of soccer extracurricular students of Junior High School 25 Pekanbaru by 59.10%, there is a contribution of eye-foot coordination to distance kicking ability. The distance of extracurricular football students of SMPN 25 Pekanbaru is 30.0%, there is a contribution of leg muscle power and eye-foot coordination to the long-distance kick ability of soccer extracurricular students Junior High School 25 Pekanbaru by 39.3%.